Development of Rembang Regency Ethnoscience-Based Integrated Thematic Teaching Material to Improve Concept Mastery - Anis, Meutia; Sarwi, Sarwi; Rozi, Fahrur (Universitas Negeri Semarang, 2021)
School plays an important role in introducing local culture by integrating culture as ethnoscience learning material. This study aimed to determine the process of developing Rembang Regency ethnoscience-based integrated thematic book to improve students' concept mastery. This study applied the R&D method by using Borg & Gall design. Data were collected through observation, interview, test, and questionnaire, and the subjects of this study were fourth grader of elementary school consisting of two experimental classes. The data were analyzed by applying feasibility, effectiveness, and practicality test of learning tool. The result of this study indicated that each indicator of ethnoscience-based thematic learning material was in very valid criteria with an average score of 90.4 (scale 0-100). Ethnoscience-based thematic learning material was effective to improve students' mastery of concept, this was proved by the completeness which reached 100%, the enhancement result was in the moderate category, and students' response was in the very high category. The result of the study proved that students were pleased and motivated during the ethnoscience-based learning process so that their concept mastery increased. From data analysis, it could be concluded that the development of ethnoscience-based integrated-thematic teaching material could improve students' mastery of concept.